The Impact of Organizational Reward on Employee Performance with Mediating Role of Motivation in Teaching Hospitals of Qazvin - Rafat Mohebbifar; Mahmood Bakhshian; Sima Rafiei (Kerman University of Medical Sciences, 2016)
Introduction: Human resources are the main sources of production and basic capital in every organization. Reward management is one of the effective approaches used by the organizations to attract and retain employees in their work place. The aim of this study was to investigate the effect of organizational reward system on performance of administrative and support employee through increasing their motivation in teaching hospitals of Qazvin, 2015. Methods: This cross-sectional descriptive-analytical study was conducted on 326 employees selected from three departments (administrative, support, and management) of 5 teaching hospitals of Qazvin in 2015. The questionnaires used in this study include demographic questionnaire (11 questions related to demographic characteristics), Waruni research questionnaire (8 questions related to organizational reward), Herzberg's two-factor questionnaire (37 questions related to employee motivation), and Stephen's research-based questionnaire (19 questions related to employee performance). Data were analyzed using SPSS 23 and LISREL 8.8. To test the study hypothesis, confirmatory factor analysis (CFA) and structural equation modelling (SEM) were applied. Results: Findings revealed that organizational reward (both extrinsic and intrinsic) had an influential effect on the employee motivation. Furthermore, either directly or with mediating role of motivation, organizational reward had a direct significant effect on employee performance (P≤0.05). Conclusion: Identification and increasing motivating factors in employees, especially those who are under more work pressure, can significantly improve their performance. Keywords: Motivation, Teaching Hospital, Organizational Reward, Performance Citation: Mohebbifar R, Bakhshian M, Rafiei S. The Impact of Organizational Reward on Employee Performance with Mediating Role of Motivation in Teaching Hospitals of Qazvin. Journal of Health Based Research 2016; 2(3): 223-232.